THE EFFECTIVENESS OF E-BUDDY IN ACCELERATING ADMINISTRATIVE SERVICES IN WONOAYU VILLAGE - Saputra, Figo Dwi; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to evaluate the effectiveness of the E-Buddy application in accelerating administrative services and strengthening digital governance in Wonoayu Village. Method: A descriptive qualitative approach was adopted, with data collected through interviews, observations, and documentation to provide an in-depth understanding of the application’s implementation. Results: The findings reveal that E-Buddy has successfully improved the efficiency of correspondence delivery and record management, thereby enhancing the productivity of village officials and contributing to more transparent administrative practices. However, the utilization of available features remains suboptimal due to limited adaptability among users and technical disruptions during system updates, which constrain its full potential. Novelty: This study highlights the dual role of E-Buddy as both an enabler of administrative modernization and a reflection of the challenges inherent in digital transformation at the village level. The novelty lies in uncovering the gap between system design and practical use, emphasizing the need for continuous training, user adaptation, and technical reinforcement to fully optimize digital administrative tools in rural governance.